Perception of Small Farmers for Adoption of Agroforestry Systems in the Tolon District of Northern Ghana - Abukari, Ammal; Larweh, Sordji (Annals of Arid Zone, 2023)
Farm characteristics and perceptions of farmers in taking up of the agroforestrypractices were studied in the Tolon district of northern Ghana during 2020. Fourcommunities; Nyankpala, Dimabi, Kpendua, and Tunayili were selected randomly and50 respondents were chosen in each community to make a sample size of 200. Personalinterviews with questionnaires, key informant interviews and field observation were usedto gather data on the field. The data were analyzed using frequency and percentagedistributions, and correlational investigations. The findings of the study revealed that34% of the responded were active in the practice of agroforestry. Further, significantrelationship was observed between respondents’ personal variables such as age, gender,educational level, and marital status and adoption of agroforestry practices (P<0.01). It isproposed that benefits of agroforestry be promoted among famers for wider adoption ofthis system and to provide adequate technical assistance to farmers who are interested inpracticing agroforestry that guaranteed efficient use of available resources on farmlandsowned by all types of landholders.